Taalseksisme as 'n vorm van eensydige leksikografie - Beyleveld, A.A.; van Jaarsveld, G.J. (Lexikos, 1991)
Language Sexism as a Form of Biased Lexicography.As an interface between linguistics and society, the dictionary serves to open up linguistics to language users in a very special way. A pragmatic approach, however, is also expected from the lexicographer, in the sense that the guidance provided in a dictionary should reflect actual language usage. A dictionary therefore has both a normative and informative character. Add to this the fact that dictionaries are used as authoritative works of reference, and the possibility that they serve to reinforce and to maintain specific language patterns is not excluded. In a period characterized by an increased focus on the prejudiced categorizing of women, the dictionary, as a source of cultural authority, is also under suspicion. The possibility that dictionaries may contribute to stereotyped roles and sexist suppositions by means of biased lexicographic practices, is discussed in this article. Words under the letter M in both a bilingual and an explanatory dictionary were studied in order to determine whether these lexicographic works are indeed guilty of linguistic sexism.